2022
DOI: 10.1177/10598405221100665
|View full text |Cite
|
Sign up to set email alerts
|

School Nurses’ Language Needs When Caring for Students from Limited English Proficiency Households

Abstract: The number of school-aged students with diverse linguistic and cultural backgrounds is increasing across the United States. This survey identifies strategies school nurses use for communicating to families with limited English proficiency and describes recommendations to improve language needs. The online survey was completed by K–12 school nurses and data were analyzed using descriptive statistics. Among the 52 participants, only 23% (n = 12) indicated that resources they were currently using to interpret hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…As the first point of contact for young people facing mental health issues, the nurse provides advice and helps young people recognize non-suicidal self-harm, activates advocacy, support, and follow-up appropriate to the situation, and documents the student's condition (Lloyd-Richardson et al, 2020). From the literature examined in this review, the role of the nurse and the team is evident in the management of students with different linguistic and cultural backgrounds (Bennett & Watts, 2022), promoting sexual health education (Dickson et al, 2020), cessation of smoking and e-cigarettes (Blume & Lines, 2020), prevention of gambling addiction (Johnson & Edwards, 2020), prevention of teenage pregnancy (Akella, 2019), prevention of suicide (Tyndall et al, 2023), and management of children experiencing situations such as trauma, nomadism, discrimination, immigration (Mazyck, 2021). School nurses support the use of evidence-based complementary and integrative therapies in the school setting (NASN Position Statement, 2023), promote School-Based Vision Programs, for childhood visual impairment (Ambrosino et al, 2023), are involved in the promotion of vaccines in a school district and in the education of families and students who are vaccine-hesitant (Wilson et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…As the first point of contact for young people facing mental health issues, the nurse provides advice and helps young people recognize non-suicidal self-harm, activates advocacy, support, and follow-up appropriate to the situation, and documents the student's condition (Lloyd-Richardson et al, 2020). From the literature examined in this review, the role of the nurse and the team is evident in the management of students with different linguistic and cultural backgrounds (Bennett & Watts, 2022), promoting sexual health education (Dickson et al, 2020), cessation of smoking and e-cigarettes (Blume & Lines, 2020), prevention of gambling addiction (Johnson & Edwards, 2020), prevention of teenage pregnancy (Akella, 2019), prevention of suicide (Tyndall et al, 2023), and management of children experiencing situations such as trauma, nomadism, discrimination, immigration (Mazyck, 2021). School nurses support the use of evidence-based complementary and integrative therapies in the school setting (NASN Position Statement, 2023), promote School-Based Vision Programs, for childhood visual impairment (Ambrosino et al, 2023), are involved in the promotion of vaccines in a school district and in the education of families and students who are vaccine-hesitant (Wilson et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Research shows the weighty social consequences tied to divergent or inaccurate translation choices and illustrates how translation choices can reproduce patterns of structural racism in social institutions (Bucholtz, 2009; Hale, 2002; Jacquemet, 2011). In schools, a failure to train interpreters or evaluate the enactment of interpreting policies may lead to inadequate translation of parental rights and informed consent requirements under the Individuals With Disabilities Education Act (IDEA; 2004) (Cheatham, 2011); and both parents and educators have raised concerns about availability, adequacy, and training of interpreters in school settings as a barrier to accessing school services such as special education and effective school nursing (Bennet & Watts, 2022; Larios & Zetlin, 2022).…”
Section: Theoretical Framework: Power In Language Policy As Negotiate...mentioning
confidence: 99%
“…Whitman et al (2010) shared that approximately three-fourths of Alabama school nurses had access to a qualified interpreter, yet half reported difficulties communicating with families with LEP. Bennett and Watts (2022) reported that school nurses in Nevada described using students to address language hurdles and the ability to communicate with parents. Matza et al (2015) explored the cultural competencies of school nurses and reported that nurses described working around language barriers due to a lack of language access resources in their schools.…”
Section: Working With Immigrant Students and Families In The School S...mentioning
confidence: 99%